Ticagrelor Does Not Improve Endothelial Dysfunction in Stable Survivors of Acute Coronary Syndrome. (September 2019) - Lim, Sungmin; Choo, Eun Ho; Kim, Chan Joon; Choi, Ik Jun; Lee, Kwan Yong; Hwang, Byung-Hee; Lee, Jong-Min; Chung, Wook Sung; Chang, Kiyuk
Background: Ticagrelor is an intriguing antiplatelet agent with a potentially beneficial impact on endothelial dysfunction and confers a mortality benefit beyond 1 month after acute coronary syndrome (ACS). However, little data exist on whether ticagrelor improves endothelial dysfunction in stable patients who survive the acute period and receive guideline-directed medical therapy. Methods and Results: This study is a prospective, randomized, parallel, open-labeled study that enrolled 30-day survivors of non-ST-segment elevation ACS (NSTE-ACS). Forty patients with NSTE-ACS were randomly assigned to ticagrelor or clopidogrel groups. The primary end point was the change in the percentage brachial artery flow-mediated dilation (baFMD) from baseline. Baseline characteristics were not different between the 2 groups. The median time from the stent implantation to screening was 269 days. After 30 days of study medication administration, the change in the percentage baFMD value was similar between the ticagrelor and clopidogrel groups (−0.08 [1.42] vs 0.30 [1.69], P = .66). There was no difference in the change in high-sensitive C-reactive protein (−0.61 [1.48] vs −0.01 [0.57], P = .28); however, the change in platelet inhibition significantly differed (P2Y12 reaction units, −140.5 [49.5] vs −3.9 [51.4], P < .001). Conclusions: This dual time point baFMD study demonstrated that treatment with ticagrelor was not superior to clopidogrel for improving endothelial dysfunction in stabilized patients with NSTE-ACS.